2020
DOI: 10.1101/2020.09.22.20199802
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Smoking is associated with worse outcomes of COVID-19 particularly among younger adults: A systematic review and meta-analysis

Abstract: Background: Smoking impairs lung immune functions and damages upper airways, increasing risks of contracting and severity of infectious diseases. Methods: We searched PubMed and Embase for studies published from January 1-May 25, 2020. We included studies reporting smoking behavior of COVID-19 patients and progression of disease, including death. We used a random effects meta-analysis and used meta-regression and lowess regressions to examine relationships in the data. Results: We identified 47 peer-reviewed… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 70 publications
(169 reference statements)
2
35
0
Order By: Relevance
“…Former smokers clearly showed similarly poor progression, while current smokers showed a clear tendency to worse progression but without statistical significance. The same results were obtained in the meta-analysis of Patanavanich et al 7 (only 8 articles divided smokers into categories). Most of the studies included in the meta-analysis have significant limitations: they are mostly retrospective and have significant selection and data biases and lack a comparative group, making it difficult to establish causality.…”
supporting
confidence: 78%
“…Former smokers clearly showed similarly poor progression, while current smokers showed a clear tendency to worse progression but without statistical significance. The same results were obtained in the meta-analysis of Patanavanich et al 7 (only 8 articles divided smokers into categories). Most of the studies included in the meta-analysis have significant limitations: they are mostly retrospective and have significant selection and data biases and lack a comparative group, making it difficult to establish causality.…”
supporting
confidence: 78%
“…Another systematic review did not summarize the results as a meta-analysis 13 . One study demonstrated only the prevalence of smokers among patients hospitalized with COVID-19 71 while in another study, the authors retrieved the studies from only one database and the definition of smoking was unclear 8 . One focused on chronic obstructive pulmonary disease (COPD) and ongoing smoking history 17 .…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this this version posted March 12, 2021. ; https://doi.org/10.1101/2021.03.11.21253207 doi: medRxiv preprint 14 is known to be associated with poorer outcomes of acute COVID-19 39 . Symptoms like fatigue or shortness of breath have initially neither been assessed by validated scoring methods nor objectivated by examinations, since at that time, the rapid acquisition of reconvalescent plasma donors was top priority.…”
Section: Discussionmentioning
confidence: 99%